PEMBUATAN BIOGAS DARI SAMPAH SAYURAN - Andreas Felix S.; Paramitha S.B.U.; Diyono Ikhsan (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Vegetable waste is produced in a huge volume everyday. The sources of this waste are traditional market, where the waste is usually unusefull or just taken by people for feeding cows. It is actually an organic waste that can be used to make biogas. The reactions of biogas reforming are included by three steps, hydrolysis reaction, acidic reaction and methanogenic reaction. At this research we use cow manure as a mixing and as starter for methanobacteria.The intention of this research are to make biogas using vegetable waste from traditional market in batch system, to know the concentration and composition of vegetable waste, water and cow manure in slurry, and also to know the heating value and volume of biogas. Tools that used are plastic tank and simple type of floating drum biodigester with manometer that is operated in room temperature, atmospheric pressure. The dependence variables are concentration of slurry within 6-10 % (dry basic weight per volume slurry) and composition 1 : 0, 1 : 0,5 and 1 : 1 weight comparison of vegetable waste with cow manure. The data of biogas volume and heating value will be observed everyday until the production of biogas stops.Biogas is produced since the first day of digestion until 35 days. The accumulation of biogas volume is reached the highest amount in 9 % of concentration and 1 : 0,5 of composition. The analysis of heating value is being measured based on the highest volume from the best consentration and composition. Biogas can be burned on the 7th day until 30th. The highest heating value of it is about 10081 Joule/day on the 18th day. This is happen during the periode of regeneration time of methanogenic bacteria which converts the acetic acid into methane.